2019
DOI: 10.1137/17m1162524
|View full text |Cite
|
Sign up to set email alerts
|

Optimality Conditions and Constraint Qualifications for Generalized Nash Equilibrium Problems and Their Practical Implications

Abstract: Generalized Nash Equilibrium Problems (GNEPs) are a generalization of the classic Nash Equilibrium Problems (NEPs), where each player's strategy set depends on the choices of the other players. In this work we study constraint qualifications and optimality conditions tailored for GNEPs and we discuss their relations and implications for global convergence of algorithms. Surprisingly, differently from the case of nonlinear programming, we show that, in general, the KKT residual can not be made arbitrarily small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Actually, we have also not established this result in the first publicly available version of this paper, although it is a natural consequence of our theory. Very recently, and citing this earlier version, Bueno, Haeser and Rojas reported this fact in a more general context, namely, of the generalized Nash equilibrium problems (see [16,Theorem 6.3]). In this sense, it is not the first time that Corollary 4.3 appears in the literature.…”
Section: Boundedness Of the Dual Sequences Generated By The Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Actually, we have also not established this result in the first publicly available version of this paper, although it is a natural consequence of our theory. Very recently, and citing this earlier version, Bueno, Haeser and Rojas reported this fact in a more general context, namely, of the generalized Nash equilibrium problems (see [16,Theorem 6.3]). In this sense, it is not the first time that Corollary 4.3 appears in the literature.…”
Section: Boundedness Of the Dual Sequences Generated By The Methodsmentioning
confidence: 88%
“…according to [15]. In this paper, we only deal with the augmented Lagrangian (1) (and then we always have (16)), but we note that the general form (15) is also appropriate for the case when a non-quadratic penalty augmented Lagrangian function is employed, as in [18,29]. It is known that when Algorithm 1 does not stop by failure, it generates an AKKT sequence for the problem (P) if its limit point is feasible (see [15]).…”
Section: Relations Between Pakkt-regular and Other Known Cqsmentioning
confidence: 99%
“…For NLPs it has been shown that this variant possesses strong convergence properties even under very mild assumptions [4,6]. It has since been applied to solve various other problems, including MPCC [7,26], quasi-variational inequalities [27], generalized Nash equilibrium problems [16,29], and semidefinite programming [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…La literatura sobre estos dos tipo de problemas asi como para EPs es amplia tanto desde el punto de vista de existencia y unicidad de soluciones, de algoritmos para hallar soluciones y de modelaje de problemas que surgen en diferentesáreas, para QVIs ver por ejemplo [9,27,18] y referencias, para GNEPs [17,16,15,14,7] y referencias, para EPs [30,33,32,6,31] y referencias. Entanto el estudio de QEP ha recibido menos atención en comparación con los problemas antes mencionados, esto puede ser debido a la complejidad y generalidad de su formulación y de aun no encontrarse suficientes problemas aplicativos que puedan ser modelados estrictamente por QEPs, y que no puedan ser modelados por algun problema que sea un caso particular de un QEP.…”
unclassified